2019
DOI: 10.1021/acsbiomaterials.9b00618
|View full text |Cite
|
Sign up to set email alerts
|

Dasatinib Promotes Chondrogenic Differentiation of Human Mesenchymal Stem Cells via the Src/Hippo-YAP Signaling Pathway

Abstract: Mesenchymal stem cells (MSCs) are progenitors of chondrocytes and could be used as a potential therapy for cartilage defects in diarthrodial joints. However, promoting chondrogenic differentiation of MSCs remains a daunting challenge. As a small molecular drug, dasatinib can promote MSC differentiation, although the exact mechanisms of chondrogenic differentiation are unclear. In this study, the differentiation of MSCs into osteoblasts, adipocytes, and chondrocytes was assessed by the protein and mRNA levels o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(23 citation statements)
references
References 39 publications
1
22
0
Order By: Relevance
“…Several studies have confirmed that YAP1 is overexpressed in OA animal model tissues, and the YAP1 content increases with the severity of OA (Nie et al, 2019;Zhang et al, 2019;Kania et al, 2020). Gong et al (2019) reached the same conclusion in studies with an OA mouse model and human OA tissue:…”
Section: Yap1 Is An Important Promoter Of Oamentioning
confidence: 63%
See 4 more Smart Citations
“…Several studies have confirmed that YAP1 is overexpressed in OA animal model tissues, and the YAP1 content increases with the severity of OA (Nie et al, 2019;Zhang et al, 2019;Kania et al, 2020). Gong et al (2019) reached the same conclusion in studies with an OA mouse model and human OA tissue:…”
Section: Yap1 Is An Important Promoter Of Oamentioning
confidence: 63%
“…Several studies have confirmed that YAP1 is overexpressed in OA animal model tissues, and the YAP1 content increases with the severity of OA ( Nie et al, 2019 ; Zhang et al, 2019 ; Kania et al, 2020 ). Gong et al (2019) reached the same conclusion in studies with an OA mouse model and human OA tissue: (1) YAP1 transcription was upregulated in knee chondrocytes of OA mice by RT-qPCR analysis; (2) YAP1 levels detected in articular chondrocytes of OA mice were upregulated by Western blot analyses; (3) and YAP1 mRNA and protein levels were increased in human chondrocytes of OA compared with normal human cartilage.…”
Section: Role Of Yap1 In Oamentioning
confidence: 90%
See 3 more Smart Citations